Samsung Galaxy Note 3 for dummies / Dan Gookin - Gookin, Dan
Learn how to use your new Samsung Galaxy Note 3-the easy way! The Samsung Galaxy Note 3 is the latest in Samsung's revolutionary line of phablet devices. But what is a phablet? In Samsung Galaxy Note 3 For Dummies, Dan Gookin explains everything you need to know about your new phone/tablet and describes how to maximize the device's performance-even if you've never owned a smartphone or tablet before! Users will love this book for the in-depth look at this great device from Samsung. From the author who wrote the first For Dummies book back in 1991 comes another funny, friendly users' guide that